KEY SOURCES OF RESEARCH OF MECHANISMS OF INFORMATION AND COMMUNICATION PROTECTION OF THE SELECTION PROCESS - Mikhailov M.O. (Pressing Problems of Public Administration, 2017)
The author of the article investigates the features of key sources of information and communication support of the electoral process, carrying out the classi cation, de ning the types and types of sources. Using the achievements of domestic and foreign scholars in this area of activity, the author reveals the role of sources in the study of the mechanisms of information and communication support of the electoral process in Ukraine.